MANAJEMEN SUMBER DAYA MANUSIA PRODUK OLAHAN BAMBU - Nanda Hidayan Sono; Rizqiyatul Hasanah Hidayan (Al-Idarah, 2021)
The tight competition in the business world requires every business actor to develop business with various kinds of competition in all fields, one of which is by processing human resources, because the quality of human resources greatly affects the quality of production. The production process is usually associated with productivity, if productivity increases it will also be followed by an increase in the performance of the company. Human Resources is one of the keys to the success of the company in order to increase competition and improve product quality. The method used in this study is a descriptive type of qualitative approach. The data collection technique was through observation, interviews and documentation, the data source being from UD Slamet Situbondo. The purpose of the study was to determine the effect of human resources on improving product quality. The results of the study indicate that the existence of quality possessed by human resources is very decisive for improving product quality in the future. For measuring product quality, it can be known through customer satisfaction, free from damage, the size of the durability of the product, product accuracy, and easy to operate and maintain. Meanwhile, from a marketing point of view, product quality is measured in terms of the buyer's perception of the quality of the product